MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN, BERPIKIR KRITIS, DAN BERBICARA MURID MENGGUNAKAN MODEL PEMBELAJARAN BERCERITA DI KELAS V SDN TELAGA BIRU 6 - Nurhapsari, Tiara; Dwitalia Sari, Dessy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low levels of learning activity and deficiencies in reading comprehension, critical thinking, and speaking skills have resulted in suboptimal Indonesian language learning outcomes for fifth-grade students. This study aimed to evaluate the effectiveness of the BERCERITA learning model in enhancing these three skills as well as student learning outcomes, employing a Classroom Action Research (CAR) approach with 14 fifth-grade students from SDN Telaga Biru 6 as participants. Data were collected through observation, interviews, and tests, and subsequently analyzed using both qualitative and quantitative methods. The results demonstrated improvements in reading comprehension and critical thinking skills from 28.6% to 92.8%, and in speaking skills from 14.3% to 92.8%. Mastery of learning outcomes also improved, with achievement rates reaching 100% in the affective and psychomotor domains and 92.8% in the cognitive domain. Thus, the BERCERITA learning model has proven effective as an alternative for enhancing the quality of Indonesian language instruction in primary schools.